Celtic language writing matters in Hispania, Gaul and Italy (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
This study aims to analyze how Lusitanian, Celtiberians, Iberians and Gauls adapted epigraphy in order to create religious inscriptions in their indigenous languages. First, we will list briefly those epigraphs consid- ered to be religious, and the different epigraphic habits will be compared, according to their chronology, writing system, material, archaeological con- text and, if possible, the content of the inscriptions, taking into account the difficulty that concerns the identification of these epigraphs. Not all the epi- graphic cultures created the same kind of religious inscriptions: they are fre- quent in some languages and provide rich information about beliefs and customs, while in other languages religion seems to be an irrelevant epigraphic topic.
Keywords: Iberian Epigraphy; Celtiberian Epigraphy; Lusitanian Epigraphy; Gaulish Epigraphy; Religious Epigraphy